O DIREITO AO TRABALHO DECENTE : sonho ou realidade? - Monaco, Luigi Lo (2012)
The thesis we have developed is focused on the right to work "decent." This is a research and ethical reflection on the threat of economic "globalization" in Brazil. The right to work and work "decent" is situated in the larger context of human rights, the evolution of labor law and the current economic situation. The text prepared reports on the rise of the bourgeoisie and the capitalist exploitation of workers, since modernity, emphasizes the limits and the positive aspects of liberal constitutions and Brazilian constitutions since 1824 until 1988, stresses the importance of workers' struggles to defend the dignity of workers and their rights. The main hypothesis formulated by the author, who supervised the research, is that the new economic context of economic "globalization" of neoliberalism and social rights and the right to work "decent" are increasingly threatened. Hence the need to defend these rights resisting the process of deterioration of labor relations and setting, from ethical references, a schedule of minimum goals to be achieved in the near future.